Hubungan Kualitas Diet dengan Kadar Glukosa Darah pada Pasien Diabetes Mellitus Tipe 2 di Kota Yogyakarta: Hubungan Kualitas Diet dengan Kadar Glukosa Darah pada Pasien Diabetes Mellitus Tipe 2 di Kota Yogyakarta - Wahyuni, Bierliana Rieska; Dewi, Agil Dhiemitra Aulia; Hariawan, Muhammad Hafizh (Amerta Nutrition, 2023)
Background: Diet quality is an important component in blood sugar regulation. Effective blood sugar regulation can effectively reduce the risk of developing additional complications and chronic diseases. The number of people suffering from type 2 diabetes mellitus (T2DM) in Yogyakarta City, Special Region of Yogyakarta (DIY) in 2021 will be 10,635 people and in 2022 it will be 15,588 people. Objectives: This study aims to determine the correlation between diet quality and blood glucose levels in Type 2 Diabetes Mellitus patients living in Yogyakarta, Indonesia. Methods: This research applied a cross-sectional design and is an analytical observational study. Purposive sampling was used to select participants, resulting in a sample size of 63 individuals. Blood glucose levels obtained from secondary sources at the Community Health Center were used as the dependent variable. The Diet Quality Index-International Questionnaire (DQI-I Q) and the Semi-Qualitative Food Frequency Questionnaire (SQ-FFQ) were used to assess the independent variables of food quality. The data was statistically analyzed using STATA version 14 and the Chi-Square test. Results: 35.38% of respondents who reported eating healthy food had normal blood glucose levels (current blood glucose levels below 200 mg/dL), while 12.3% of respondents who reported eating poor food reported hyperglycemic blood glucose levels (current blood glucose levels exceeding 200 mg/dL). In T2DM patients, there was no association between dietary quality and blood glucose levels (p-value=0.397). However, correlations could be observed between blood glucose levels and DQI-I variation components (p-value=0.000) and overall balance (p-value=0.018). Conclusions: In contrast to transient blood glucose levels, the overall component of variation and balance was related to diet quality.